Research Progress on Resveratrol Production by Recombinant Engineering Bacteria Fermentation - Wenye XIE; Yuan LI; Wanbin ZHU; Fengying GU; Bo JIAO; Qiang WANG (Shipin gongye ke-ji)
Resveratrol, as a non-flavonoid polyphenol organic compound, has antioxidant, anti-aging, anti-inflammatory, anti-cancer and other functions, and has shown broad application prospects in the food, medicine, and cosmetics industries. Researchers have successfully designed and constructed an efficient heterologous synthesis pathway in microorganisms, and realized the industrial production of resveratrol by large-scale fermentation combined with engineered strains. In this paper, based on the frontier progress in the research of resveratrol biosynthesis, the biosynthetic pathway, the chassis of recombinant engineering bacteria, and the optimization strategy of synthesis methods are reviewed. Two recombinant engineering bacteria, yeast and Escherichia coli, commonly used in the production of resveratrol are introduced and compared. The optimization strategy of resveratrol biosynthesis is proposed from three aspects: The expression of key enzymes, precursors and fermentation processes of resveratrol synthesis. This paper summarizes the existing problems and future development directions, in order to provide theoretical support and reference for the efficient and green biomanufacturing of resveratrol, so as to meet the growing market demand, promote the industrial application of resveratrol in the food industry, and promote the high-quality and sustainable development of the food industry in the future.